Removal of Phenol by Ozonation in Strongly Alkaline Conditions using a Jet Loop Reactor Operated in Continuous Phase - Barlak, Melahat Semin; Cengiz, Ibrahim; Degermenci, Nejdet; Yildiz, Ergun (Wiley, 2025)
AbstractIn this study, phenol removal by ozonation under strong alkaline conditions in a continuously operated jet loop reactor (JLR) is investigated. The effects of inlet ozone gas concentration, hydraulic retention time (HRT), and influent phenol concentration on phenol, chemical oxygen demand (COD), and total organic carbon (TOC) removal in the JLR effluent are evaluated. When the inlet ozone gas concentration is 17.5 gO3 m−3, the steady‐state phenol, COD, and TOC removal efficiencies are determined as 97.8%, 61.1%, and 32.2%, respectively. When the inlet ozone concentration increases from 17.5 to 56.5 gO3 m−3, phenol is not detected in the JLR effluent. The system operates at different HRTs, and the highest removal efficiency at steady‐state is obtained at 8 h HRT. While phenol is completely removed at this HRT, COD and TOC removals are 76.8% and 48.2%, respectively. An increase in phenol concentration in the JLR influent leads to a reduction in the phenol, COD, and TOC removal efficiencies in the steady‐state effluent.
Keywords: Research Article